An Old Diaspora: Histories of Militancy by Palestinians with a Northeastern Accent. (May 2019) - de Oliveira, Luciana Garcia
Most of the Palestinians who arrived in the cities of Northeastern Brazil came during the time of the Ottoman Empire in the nineteenth century, especially after the travels of Emperor Dom Pedro II. The arrival of Palestinians before the founding of the State of Israel in 1948 made many Palestinians and their descendants indifferent to the Israeli-Palestinian conflict. The situation changed in the 1980s as a result of the worsening situation of Palestinians in Lebanon, when the Palestine-Brazil Cultural Center was established in the city of Olinda, Pernambuco, and the deputy Raymundo Asfora made many speeches in defense of the Palestinian cause. These militant actions served as an inspiration for new generations of Palestinians born in Brazil. A maioria dos palestinos que chegaram à algumas cidades do nordeste brasileiro vieram durante a vigência do Império Turco Otomano, em pleno século XIX, sobretudo após as viagens do imperador do Brasil, Dom Pedro II ao Oriente Médio. A chegada dos palestinos antes da fundação do Estado de Israel (1948) foi determinante para que muitos palestinos e descentes fossem indiferentes ao conflito Israel-Palestina. A situação mudou, mais tarde, na década de 1980, durante o agravamento da situação dos palestinos no Líbano. Foi inaugurado o Centro Cultural Palestina-Brasil na cidade de Olinda, PE, e o deputado Raymundo Asfora realizava muitos discursos públicos em defesa da causa palestina. Essas ações militantes serviram de inspiração para as novas gerações de palestinos nascidos no Brasil.